Pengembangan E-Book Tata Rias Wajah Pengantin Barat (European Bridal) Berbasis Canva - Agnesia, Dinda; Hidayah, Nurul; Arum, Aniesa Puspa (Jurnal Ilmiah Wahana Pendidikan, 2023)
E-books are one of the learning media resulting from the adaptation of digital manuals which can also be used as learning resources. Based on the results of a needs analysis conducted on 36 students of the active Cosmetology Education study program, it was found that 66.7% of students stated that Western Bridal Makeup was the most difficult makeup to practice and 97.4% stated that digital learning media was needed. The aim of developing the Canva-based European Bridal Makeup e-book is to serve as additional learning media in digital form and additional learning resources suitable for use by students of the Makeup Education study program.The method used in this research is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate) by Thiagarajan. The validity test was carried out by media experts and material experts. The assessment instrument used is a validation sheet consisting of various aspects of the assessment using a Likert scale.The e-book is declared feasible after passing through several revisions from experts. Based on the results of the validation test by material experts with a value of 92% or included in the ''Very Valid'' criteria and by media experts with a value of 95% which is also included in the ''Very Valid'' criteria.